Simple Parametric Model for Calculation of Lateral Electromagnetic Loads in Tokamaks at Asymmetric Vertical Displacement Events (AVDE) - Sergey Sadakov; Fabio Villone; Guglielmo Rubinacci; Salvatore Ventre (Plasma, 2022)
This paper describes a family of relatively simple numerical models for calculation of asymmetric electromagnetic (EM) loads at all tokamak structures and coils at asymmetric vertical plasma displacement events (AVDE). Unlike currently known AVDE studies concentrated on plasma physics, these models have a practical purpose to calculate detailed time-dependent patterns of AVDE-induced EM loads everywhere in the tokamak. They are built to intrinsically assure good-enough EM load balance (opposite net forces and torques for the Vacuum Vessel and the Magnets with zero total for the entire tokamak), as needed for consequent simulation of the tokamak’s dynamic response to AVDE, as well as for the development of tokamak monitoring algorithms and tokamak simulators. To achieve these practical goals, the models work in a manner of parametric study. They do not intervene in details of plasma physics, but run at widely varied input assumptions on AVDE evolution and severity. Their outputs will fill a library of ready-for-use lateral EM loads for multiple variants of AVDE evolution and severity. The tokamak physics community can select any variant from the library, and engineers can pick ready-for-use AVDE loads. Investigated here, EM models represent one already known approach and one newly suggested. The latter attempts to reflect the helical pattern of halo currents in plasma and delivers richer outcomes and, thus, can be preferred as the single practical model for parametric calculations.